Prevalence and Distribution of Oral Conditions among Dental out Patients Children Aged 0–13 Years Attending Khanzad Polyclinic Center in Erbil City - Banaz A. Abdullah; Shaheen A. Ahmed; Ali F. Mohammad Alzubaidee (Polytechnic Journal)
Prevalence studies on oral conditions affecting children are rare worldwide, and none of them was conducted in in Erbil/Kurdistan region/Iraq. The aims in the this study were to determine the prevalence and distribution of oral conditions which include both lesions and normal variations in group of patients referred to a main, public specialized poly clinics dental center. A prospective cross-sectional study was performed, the including data collected were age, gender, and site of a condition. The examination of the patients was performed under standardized conditions; using artificial light, disposable gloves, retractors, and mirror with sterile gauze to hold tip of the tongue. Statistical analysis was performed using Statistical Package for the Social Sciences (SPSS) version 22; Fisher’s exact test; and Chisquare test. A sample of 520 children, aged range (0–13) years included in this study, 265 (51.0%) were males and 255 (49.0%) were females, divided into three age groups; 100 (19.2%) were <5 years, 274 (52.7%) were 5–9 years, and 146 (28.1%) were 10–13 years. The prevalence of oral conditions was significantly higher in 5–9 years (52.7%). The most commonly clinically diagnosed oral conditions were fissure tongue (13.1%), followed by gingivitis (9.0%) and dentoalveolar sinus (8.3%). As a first study in this age group in Erbil/Kurdistan region/Iraq, oral conditions are relatively common in the sample examined; dentist and dental practitioner should be aware for their recognition and referral for management.